The Pooled Cut-off Point of Waist Circumference as Core Component of Metabolic Syndrome Diagnosis among the Iranian Population; a Systematic Review and Meta-Analysis - Shojaeefar, Ehsan; Malih, Narges; Hossieni, Jalil; Raeisi, Sajjad; Esteghamati, Alireza (Archives of Men’s Health, 2021)
Introduction: According to a nationwide study, one-third of the Iranian population suffer from metabolic syndrome (MetS). The most controversial criteria for the diagnosis of MetS is central obesity which would be defined by waist circumference (WC) and needed to be gender and ethnic-specific. There are several national studies that reported different cut-offs for WC so the present study aimed to do a systematic review and meta-analysis to achieve an overall statistical estimate of WC for the Iranian population. Method: A comprehensive search was conducted in international databases from inception to June 2020. The search keywords were waist circumference AND metabolic syndrome AND cut AND Iran. We used the QUADAS-2 tool for quality assessment and the HSROC model for estimating pooled specificity, sensitivity, and the cut-off point from included studies in R software. Results: A total of 3571 studies were evaluated and 24 studies fulfilled the inclusion criteria. Finally, 8 studies were included. All the studies were cross-sectional. Studies with missing MetS prevalence were excluded. Most of the studies had an unclear risk of bias in patient selection. There was a wide variation among reported cut-offs for WC from national and original studies. The Pooled cut-off points of WC for the diagnosis of MetS was 90.55 cm (95%CI: 90.51-90.60) in men and 89.24 cm (95%CI: 89.13-89.36) in women. The pooled sensitivity and specificity in men were 0.67 and 0.68, respectively and the pooled sensitivity and specificity in women were 0.61 and 0.57, respectively. Conclusion: Our results were highly consistent with the only national study and the only consensus about WC cut-off. Further nationwide studies are suggested to be involved in a Mata-analysis for calculating more precise WC cut-off.